PARAMETRIC ANALYSIS OF ENERGY EFFICIENCY IN DOUBLE SKIN FAÇADES FOR HOT AND DRY CLIMATES: A CASE STUDY OF KEBBI STATE, NIGERIA - Wurma, Gambo Bara'u; Muhammad, Abdulsalam Abdullahi (FUDMA Journal of Sciences, 2024)
This research evaluates the energy and concepts of Double Skin Façades, which were established through computational simulations integrated with some relevant examples. DSF is regarded as one of the best solutions in realizing the interface between the interior and the exterior building spaces. It also allows provides architectural flexibility in the design. Recently, the double-skin façade has received much attention as opposed to the more typically glazed curtain wall. This is for its ability to effectively reduce the thermal transmission (U-value) and solar heat gain (G-value). DSF design comprises assessments of building geometric factors, glazing type, ventilation procedures, shading devices, daylighting aesthetics, and maintenance expenses. However, the concept of DSF is sometimes complicated, and its use and function influence different parameters of the building, but if the approach is overall and the aims to be realized are distinct, then the stated method is flexible enough to reach climatic variations for the greatest types of building use. Besides the fact that large number of researches carried out on the performance of this facade configuration in moderate climates, it is very vital to recognize its performance and viable formations in hot and dry climates. It is therefore a chance to learn about this facade arrangement earlier the technology is transmitted into construction in hot arid areas. Results of the analysis revealed that variation in value by certain degrees and alteration of some parameters has a direct effect in the energy use intensity as well as the illuminance values of an office building...